Crystal structure of lu,[i'-bis(trimethylammonio)bis[tetra-ix¬trimethylammonio(aquacopper)(triaquaneodynium)] decaperchlorate dihydrate at -50°C - Ming Chen, Xiao-'; Seik Weng, Ng (Malaysian Journal of Science, 1999)
In the crystal structure of p.,[t'-bis(trimethylammonio)bisftt,11' 4.1,',11:"-tetrakistrimethyl- ammonio(aquacopper)(triaquaneodynium)] decaperchlorate dihydrate [P-1: a = 15.865(6) A, b = 15.29(1) A, c = 12.608(3) A, a = 105.04(4)°, p = 100.88(4)°, y = 110,13(4)°], the copper(II) atom shows square pyramidal coordination and the neodynium(III) atom tricapped trigonal prismatic coordination. The cations, anions, coordinated and lattice water molecules are linked by hydrogen bonds into a one-dimensional chain.